Fabrication of complex 3D polymer structures for cell-polymer hybrid systems - Park, Jungyul; Kim, Jinseok; Roh, Dukmoon; Park, Sukho; Kim, Byungkyu; Chun, Kukjin (IOP PUBLISHING LTD, 2006)
This paper presents a new technique to fabricate three-dimensional thin polymer structures with different geometries on each side for cell-polymer microstructures. To make complex 3D polymer structures, we manufacture a 3D-micromolding aligner, which can make two molding masters be aligned within 2 mu m and allows for applying high pressure to construct thin membranes of less than 20 mu m. Using this system, wafer-level fabrication of thin polymer structures with complex 3D geometries is realized successfully. Generally, 3D polymer microstructures are used in microfluidic systems, such as micromixers, valves and pumps. In this study we demonstrate some applications for these 3D structures as versatile cell-based microsensors for understanding structural and functional changes of cells and as hybrid organic-inorganic actuators that can be operated independently without external power sources.
Keywords: PDMS